Association of Odor Identification Ability With Amyloid-β and Tau Burden: A Systematic Review and Meta-Analysis - Tu, Lihui; Lv, Xiaozhen; Fan, Zili; Zhang, Ming; Wang, Huali; Yu, Xin (Frontiers in Neuroscience, 2020)
Background: The associations between olfactory identification (OI) ability and the Alzheimer's disease biomarkers were not clear. Objective: This meta-analysis aimed to examine the associations between OI and Aβ and tau burden. Methods: Electronic databases (PubMed, Embase, PsycINFO, and Google Scholar) were searched until June 2019 to identify studies that reported correlation coefficients or regression coefficients between OI and Aβ or tau levels measured by positron emission tomography (PET) or cerebrospinal fluid (CSF). Pooled Pearson correlation coefficients were computed for the PET imaging and CSF biomarkers, with subgroup analysis for subjects classified into different groups. Results: Nine studies met the inclusion criteria. Of these, five studies (N = 494) involved Aβ PET, one involved tau PET (N = 26), and four involved CSF Aβ or tau (N = 345). OI was negatively associated with Aβ PET in the mixed (r = −0.25, P = 0.008) and cognitively normal groups (r = −0.15, P = 0.004) but not in the mild cognitive impairment group. A similar association with CSF total tau in the mixed group was also observed. No association was found between OI and CSF phosphorylated tau or Aβ42 in the subgroup analysis of the CSF biomarkers. Due to a lack of data, no pooled r value could be computed for the association between the OI and tau PET. Conclusion: The associations between OI ability and Aβ and CSF tau burden in older adults are negligible. While current evidence does not support the association, further studies using PET tau imaging are warranted.